2015
DOI: 10.1371/journal.pone.0132738
|View full text |Cite
|
Sign up to set email alerts
|

Manganese Supplementation in Deer under Balanced Diet Increases Impact Energy and Contents in Minerals of Antler Bone Tissue

Abstract: Bone ash, collagen, Ca and P composition, are considered the main factors affecting mechanical properties in bones. However, a series of studies in bone and antler have shown that some trace minerals, such as manganese, may play a role whose importance exceeds what may be expected considering their low content. A previous study showed that a reduction in manganese in antlers during a year of late winter frosts led to generalized antler breakage in Spain, which included a reduction of 30% of cortical thickness,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 38 publications
(72 reference statements)
2
16
0
Order By: Relevance
“…Specimens for mechanical testing were first subjected to a procedure to standardize humidity content as described in Cappelli et al (). This way, the bone bars had homogeneous humidity content when they were tested.…”
Section: Methodsmentioning
confidence: 99%
“…Specimens for mechanical testing were first subjected to a procedure to standardize humidity content as described in Cappelli et al (). This way, the bone bars had homogeneous humidity content when they were tested.…”
Section: Methodsmentioning
confidence: 99%
“…This study also showed that there was a difference in Cu content between the two types of antlers assessed. Recently, Cappelli et al (2015) have shown very similar effects opposite to Mn deficiency in many antler characteristics and, again, an effect in the antler Cu content. However, no study has tried to assess the effect of supplementation with Cu injections on mechanical and structural properties and mineral composition of antler or other types of bones.…”
Section: Introductionmentioning
confidence: 78%
“…Thereafter, to standardize humidity content, the bars were dried at 20°C and 40% of relative humidity for 72 hours. The bars, that had thus homogeneous humidity content, were tested in 3-point bending with the periosteal side in tension as indicated by Cappelli et al (2015) in a Zwick/Roell 500N machine (Germany), set at 32 mm/min head speed and 40 mm gauge length.…”
Section: Mechanical Bone Propertiesmentioning
confidence: 99%
See 2 more Smart Citations